EFFECT OF TEMPERATURE AND SLICE SIZE ON AVOCADO PULP DRYING RATE AND OIL YIELD - Temu, Abraham T (Tanzania Journal of Engineering and Technology, 2017)
The effect of temperature and slice thickness on avocado pulp drying rate and oil yield was determined at 50 o C, 60 o C and 70 o C. Pulp slices of 2mm and 5 mm thick were used. The avocado pulp was found to contain 74-75% (wet basis) water, which makes extraction of oil by both chemical and mechanical means difficult. Experimental results showed that oil yield increased with decreasing moisture content reaching a yield of 61% at 10% moisture content. The rate of drying increased with temperature, but decreased with slice thickness. The drying data obtained agreed well with several thin-layer drying models. The models showed that the characteristic drying constant increased linearly with drying temperature and decreased with slice thickness. The Physico-chemical properties of the obtained oil compared favorably with those obtained from other conventional seed oils.